A cross-sectional, qualitative study using the Pecking Order Theory to describe the importance of cash flow management on the sustainability of SMEs in Durban - Naicker, Vidya (The IIE, 2020)
The engine room of a modern economy requires that small businesses, an integral part of the economy, function optimally in order to support the overall health of the economy. The South African context of a developing economy and severe resource limitations means, small businesses provide a significant and tangible impact on the general economic conditions and well-being of our society. The purpose of this crosssectional qualitative study was to gain an in-depth understanding of the importance of cash flow management in small and medium-sized businesses, as well as how this would impact the sustainability of these businesses. This study critically examines Myer and Maljuf’s (1984) Pecking Order theory and evaluates its application in terms of SME’s sources of funding preferences. This research examined the importance of financial management in small businesses and how cash management practices would impact these businesses. This research seeks to advance the body of knowledge related financial management and may assist SME owners/managers in improving the sustainability of their businesses. Any improvement in the sustainability of the small business sector of South Africa will have a positive impact on the country’s general economic conditions.
Keywords: Pecking Order Theory; Small and medium enterprises (SMEs); Cash flow management; Sustainability; Durban